Variasi Ungkapan Permohonan oleh Pembelajar Bahasa Jepang - Indraswari, Thamita Islami; Meisa, Wistri (Universitas Muhammadiyah Yogyakarta, 2018)
ABSTRACTThis article examine language variation of irai hyogen used by the Japanese language learners of Japanese Language Education Department in Universitas Muhammadiyah Yogyakarta. In this study, language variations are focused in what expressions are being used as irai hyogen and how are the flow of expressions in two different settings, which is 1) irai hyogen being used by student to teacher, 2) irai hyogen being used by junior student (kohai) to senior student (senpai). The study employs qualitative-descriptive method with open-ended questionnaire as instrument, distributed to 21 people. The data are analyzed by using open coding model of Strauss and Corbin. The findings of the study showed that for irai hyogen expressed to sensei, there are twelve variations of irai hyogen and ten ways of expressing irai hyogen used by learners. Meanwhile for irai hyogen expressed to senpai it is found that learners use eight variations of irai hyogen and ten ways of expressing irai hyogenÂ